Pengaruh Beban Kerja, Kemampuan Kerja, dan Lingkungan Kerja terhadap Kinerja Pegawai BPKD Kabupaten Bireuen - Sahputro, Mahyar; Syahriani, Endang; Mangkuwinata, Denny Sumantri (Singkite Journal, 2025)
Performance issues became the focus of attention, examining aspects of workload, work capability, and work environment. The research was conducted at the Bireuen Regency Regional Development Planning Agency (BPKD), using descriptive and verification methods with a quantitative approach. The data collection technique used was a questionnaire. Data analysis used multiple regression. The results found: (1) Workload, work capability, and work environment partially influence employee performance improvement, with the equation Y = 51.254 + 0.392 X1 + 0.366 X2 + 0.717 X3. (2) Workload, work capability, and work environment simultaneously contribute to employee performance improvement by 44 percent.